An ichthyofaunal amendment with the length-weight relations and condition factors of some endemic and invasive freshwater fishes from Western Anatolia - Kurtul Irmak; Kaya Cüneyt; Şen Arda; Özcan Ceylin; Ercivan Deniz; Demiral Kaan; Güngör Melike; İlhan Ali; Sarı Hasan Musa (Oceanological and Hydrobiological Studies)
In the scope of this study, fish fauna of Küçük Menderes River and its tributaries, updated with the comparison of the recent ichthyofaunal studies, as well as the length-weight relations (LWR) and condition factors (CF) were estimated for 7 freshwater fish species belonging to six families from the river basin: endemic Oxynoemacheilus eliasi, Cobitis fahireae; invasive, Carassius gibelio, Atherina boyeri, transloce Perca fluviatilis and the native Squalius fellowesii, Cyprinus carpio. The fish samples were collected with various fishnets and DC electro-fishing devices from six stations in 2018 and 2019. The LWR of the fishes was studied based on 379 specimens. The estimated values of parameter b ranged from 2.884 (A. boyeri) to 3.176 (C. fahireae). The coefficient of determination (R2) was changed between 0.792 to 0.980 for all sampling localities. In the study, Fulton’s condition factor ranged between 0.391 (S. fellowesii) to 3.080 (S. fellowesii); the relative condition factor ranged between 0.346 (O. eliasi) to 2.746 (S. fellowesii), respectively. This research is anticipated to contribute valuable insights for the conservation of the species, while also furnishing essential data to inform future fisheries management studies in the region.